2021
DOI: 10.1016/j.jaapos.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute abducens nerve palsy following COVID-19 vaccination

Abstract: We report the case of a healthy 59-year-old woman who presented with an acute abducens nerve palsy 2 days after receiving the Pfizer-BioNTech COVID-19 vaccine. In adults, such palsies are typically caused by microvascular disease or compressive tumors, although they have also been described after routine vaccinations. Given the temporal relationship between vaccination and the onset of symptoms, the lack of preexisting medical conditions, and unremarkable magnetic resonance imaging, the patient’s abducens nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 10 publications
0
63
0
1
Order By: Relevance
“…[105][106][107] Acute macular neuroretinopathy has been reported following the ChAdOx1 nCoV-19 vaccination, 108,109 and CNVI palsy has been reported 2 days after BNT162b2 mRNA vaccine (Pfizer), which resolved after 3 months. 110 Fan et al reported a case of branched retinal artery occlusion with features of paracentral acute middle maculopathy in a pediatric patient after BNT162b2 vaccination (personal communication). As of May 2021, the Royal College of Ophthalmology has issued a safety alert soliciting reports of vaccine-related retinal vascular occlusions due to an increased incidence of central venous sinus thrombosis and other anecdotal reports of RVO after vaccination.…”
Section: Potential Systemic and Ocular Side Effectsmentioning
confidence: 99%
“…[105][106][107] Acute macular neuroretinopathy has been reported following the ChAdOx1 nCoV-19 vaccination, 108,109 and CNVI palsy has been reported 2 days after BNT162b2 mRNA vaccine (Pfizer), which resolved after 3 months. 110 Fan et al reported a case of branched retinal artery occlusion with features of paracentral acute middle maculopathy in a pediatric patient after BNT162b2 vaccination (personal communication). As of May 2021, the Royal College of Ophthalmology has issued a safety alert soliciting reports of vaccine-related retinal vascular occlusions due to an increased incidence of central venous sinus thrombosis and other anecdotal reports of RVO after vaccination.…”
Section: Potential Systemic and Ocular Side Effectsmentioning
confidence: 99%
“…Similarly, antibodies against spike proteins and activated Th1 cells can cross-react with proteins and antigens in the outer retinal layers, retinal pigment epithelial cells, and large arteries, which may induce AZOOR and AAION [26]. Other possible effects induced by mRNA vaccines include microangiopathy, localized vasculitis, and demyelination, which cause the presence of eyelid purpuric and ecchymotic lesions and abducens nerve palsy [11,30].…”
Section: Mrna Vaccinesmentioning
confidence: 99%
“…MRI of the brain and orbit was unremarkable. The patient was diagnosed with right abducens nerve palsy [30].…”
mentioning
confidence: 99%
“…A healthy female who received the BNT162b2 vaccine and presented with isolated abducens nerve palsy 2 days post-vaccination was reported [ 54 ]. No details on the persistence of the palsy were provided in the report.…”
Section: Covid-19 Vaccine-associated Ocular Inflammationmentioning
confidence: 99%